Design and analysis of power supply and information transfer to three-axis gyroscope stabilizer platform; MATEC Web of Conferences; Vol. 48 : Space Engineering - Belyanin L. N. Lev Nikolaevich; Ket Vu Doan; Pozharskiy T. Timofey; Trong Yen Nguyen (Spacecrafts and Devices, 2016)
Title screen